Exploring Indian wheat genotypes for less Celiac disease toxic epitopes - Narwal, Sneh; Sharma, Bunty; saini, Ritu; Singh, Ram Baran; Gupta, Om Prakash; Pandey, Vanita; Ram, Sewa; Singh, Gyanendra Pratap (Journal of Cereal Research, 2025)
The conflicting results on the immunogenicity of ancient and modern wheat varieties highlights the need to screen the large wheat germplasm available including different wheat species, wild relatives and synthetics. The identified genotypes with low CD toxicity can be used in breeding programmes for reducing CD toxic epitopes in high yielding varieties. This study is a very small initiative where only one monoclonal antibody against few epitopes has been used. More monoclonal antibodies can be used in future studiesto target more CD toxic epitopes.The most important challenge while developing a new genotype with low CD toxicity either by breeding or genetic engineering will be to keep the baking and processing quality of the wheat intact.This will bring less CD toxic wheat products in food chain with consequences of reduced celiac disease DOI.10.25174/2582-2675/2020/89975